Validation of the Polish version of the World Health Organization Disability Assessment Schedule (WHODAS 2.0) in an elderly population (60–70 years old). Issue 3 (3rd July 2018) - Ćwirlej-Sozańska, Agnieszka; Wilmowska-Pietruszyńska, Anna; Sozański, Bernard
Abstract : Purpose . To assess the reliability and validity of the Polish version of the 36-point World Health Organization Disability Assessment Schedule (WHODAS 2.0) in an elderly population. Method . One thousand randomly selected individuals, aged 60–70 years, living in south-eastern Poland were assessed using the Polish version of the WHODAS 2.0. Results . The analysis confirmed the high reliability and validity of the tool. Cronbach's α index was 0.89. The tool had high stability, and the correlation between test and retest results was high. The relevance of the domain selection was high or very high. A factor analysis confirmed the relevance of assigning questions to domains. High theoretical relevance was also demonstrated. Statistically significant differences between those who were and were not suffering from health problems were observed. An analysis of the internal structure of the WHODAS 2.0 revealed strong correlations between the components of each domain and the final result. Conclusion . The Polish version of the WHODAS 2.0 showed high reliability and validity; thus, it can be used to assess health, functioning and disability in the elderly population of Poland.